Supercritical carbon dioxide extraction of Melaleuca cajuputi leaves for herbicides allelopathy: Optimization and kinetics modelling - Kueh, B.W.B. (Elsevier Ltd, 2018)
Due to the rice production problem, control of paddy weeds with the use of allelopathy as active compounds serve as new alternative for sustainable weeds management. The volatile oil from Melaleuca cajuputi which has possible active allelopathy compound present is extracted and analyzed. Response Surface Methodology (RSM) with central composite rotatable design (CCRD) is used to design the experiment for optimization of supercritical carbon dioxide (SC-CO2) extraction of volatile oil from Melaleuca cajuputi leaves for maximum oil yield. Three factors which included carbon dioxide (CO2) flow rate (4â7 ml/min), temperature (40â55 â) and pressure (14â26 MPa) were investigated. The regression model shows a good prediction with coefficient of determination, R2 of 0.9607. The optimum condition of SC-CO2 extraction is determined to be at CO2 flow rate of 5.88 ml/min, temperature of 43.10â and pressure of 24.91 MPa with the prediction yield of 1.24 wt. The optimum condition is validated with experimental runs which gives an average yield of 1.26 wt which indicates good agreement between the measured and predicted value. The chemical composition of the volatile oil at optimized condition is analyzed using Gas Chromatography Mass Spectrometry (GCâMS) and Gas Chromatography with Flame Ionization Detector (GC-FID). Caryophyllene and humulene are the two major sesquiterpenes detected from the optimized condition. Thus, volatile oil extract from the foliage of Melaleuca cajuputi can be considered as potential source for bio-herbicides due to the presence of caryophyllene which has allelopathic effect. Kinetics studies are also studied with modified Reverchon-Sesti Osseo as the model fitting. Â© 2018